2020
DOI: 10.3390/jcm9020606
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Burn Eschar Pericytes

Abstract: Pericytes are cells that reside adjacent to microvasculature and regulate vascular function. Pericytes gained great interest in the field of wound healing and regenerative medicine due to their multipotential fate and ability to enhance angiogenesis. In burn wounds, scarring and scar contractures are the major pathologic feature and cause loss of mobility. The present study investigated the influence of burn wound environment on pericytes during wound healing. Pericytes isolated from normal skin and tangential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 98 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…Given that Atg7‐deficient mice died within postnatal day 1, 19 we considered using the conditional Atg7 knockout model for the current study. Myofibroblasts, as the major source of excessive ECM synthesis under the pathophysiological conditions that characterize fibrosis, are the critical effector cells in the pathological process of radiation fibrosis 20,21 . Therefore, we decided to conditionally knock out Atg7 in myofibroblasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that Atg7‐deficient mice died within postnatal day 1, 19 we considered using the conditional Atg7 knockout model for the current study. Myofibroblasts, as the major source of excessive ECM synthesis under the pathophysiological conditions that characterize fibrosis, are the critical effector cells in the pathological process of radiation fibrosis 20,21 . Therefore, we decided to conditionally knock out Atg7 in myofibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Myofibroblasts, as the major source of excessive ECM synthesis under the pathophysiological conditions that characterize fibrosis, are the critical effector cells in the pathological process of radiation fibrosis. 20,21 Therefore, we decided to conditionally knock out Atg7 in myofibroblasts. In this way, the potential effect of autophagy on the process of radiation fibrosis can be evaluated in a more convincing way.…”
Section: Introductionmentioning
confidence: 99%
“…Periostin was explored in a mouse wound-repair study, where signaling through integrin molecules was shown to promote the proliferation and migration of fibroblasts [59]. Another study detected overexpression of this peptide in the pericytes of burned skin, and its function was related to scar formation and fibrosis [60]. Gelsolin function is related to actin modulation and clearance after tissue injury [61].…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms can rapidly colonize the burn wounds due to thermal destruction of the skin barrier. Burn eschar (avascular necrotic tissue) caused by deep partial-thickness and full-thickness burns provides a protein-rich niche for bacterial colonization and proliferation [ 31 , 32 ]. In addition, burn eschar may also increase the risk of infection by inhibiting early healing via basic fibroblast growth factor-induced endothelial cell proliferation and sprouting [ 33 ].…”
Section: Reviewmentioning
confidence: 99%